Impact of Liberalization on Education - Islam, Ziaul (Prabandhan: Indian Journal of Management, 2010)
The rapid development due to General Agreement on Trades in services (GATS) as well as other agreements certified have led to an increased emphasis on trade services in this era of globalization. It's GATS which focus on trade services agreements and which was wholly administered by the 154 member countries i.e a powerful organization of World Trade Organization (WTO), off these, Education is one of the 12 services which was covered by the GATS. Consequently, academic interest in Education has increased, as has been demonstrated by several special issues of education related journals . It is because of GATS that USA has generated much revenue (i.e 30 billions US dollars in 1999) from the export of education services, thereby making it the country's fifth largest service sector exports (Gabriel, 2005). Recently, OECD study(Larsen et al, 2002) estimated that values of trade in education services was about $US 30billions in 1999. In the interim, there is an initial body of empirical research in impact of liberalization of education. However, this research stems from several disciplines and is scattered throughout numerous journals. The purpose of this paper is, therefore, to provide a review of this literature and to identify implications for further research that can enhance the understanding of the impact of liberalization on education.